TRANSFER OF LAND RIGHTS BASED ON FRAUDULENT GIFT DEEDS ISSUED BY PPAT (CASE STUDY SUPREME COURT DECISION NUMBER 895 K/PDT/2023 AND NUMBER 2268 K/PDT/2017) - Ruth Dewi F. Sinambela; Tan Kamello; Rosnidar Sembiring (International Journal of Social Science, Educational, Economics, Agriculture Research and Technology (IJSET), 2025)
Land plays an important role in life, both as a place to live, a source of livelihood, and an economic asset. The transfer of land rights is often the subject of legal disputes, one of which is through grants regulated in Article 1666 of the Civil Code, where grants are the transfer of goods free of charge. Although it has been clearly regulated, grants often cause legal problems, especially if there is forgery of the deed of grant by the PPAT. For example, Supreme Court Decision Number 895 K/PDT/2023 and Decision Number 2268 K/PDT/2017 which discuss land disputes due to forgery of deed of grant. The problems raised in this thesis are: the validity of the transfer of land rights through a deed of grant by the PPAT, the process of making a deed of grant by the PPAT, and an analysis of the judge's legal considerations regarding fake deed of grant in several court decisions. The research method used is normative juridical with a descriptive analytical approach. The data used is secondary data, including primary, secondary, and tertiary legal materials. Data collection was carried out through literature studies and interviews. The analysis was carried out qualitatively by drawing deductive conclusions to answer the research problems. The results of this study show that the Deed of Grant Number 400/2006 and Number 34/2003 are fake. As a consequence, the sale and purchase of land that occurred on the basis of the deed is invalid and has no legal force. In Supreme Court Decision Number 895 K / PDT / 2023 it was proven that the Deed of Grant Number 400/2006 was fake. Therefore, the Deed of Sale and Purchase of Land that occurred on the basis of the deed of grant is invalid and has no legal force. Thus, the sale and purchase act is null and void. In Supreme Court Decision Number 2268 K / PDT / 2017 it has been proven that the Deed of Grant Number 24/2003 is fake and that the transfer of rights is invalid, making the deed of sale and purchase of the object of the dispute also invalid and has no binding legal force. In addition, the Supreme Court stated that the resistance of the fugitives was unacceptable because the resistance was filed after the auction of the disputed object was completed. The Supreme Court considered that the legal efforts made by the fugitives were formally flawed, so the cassation was granted and the resistance was considered unacceptable.